The Religious Curricula of Moroccan Fundamentalist Movements: "Justice and Spirituality" and "the Call to Quran and Sunnah" - Diouane, Hicham (Multicultural Islamic Education Review, 2024)
Moroccan fundamentalist movements employ distinct religious curricula as tools for indoctrinating their ideologies. While some subjects align with formal religious institutions, others are either adopted or omitted to adhere to the movements' beliefs and objectives. This article employs a qualitative methodology with a phenomenological and pedagogical approach to compare the religious curricula of two prominent religious agents: "Justice and Spirituality" and "The Call to Quran and Sunnah." The study seeks to unveil the main aspects of their religious Curricula and understand the internal dynamics of Moroccan fundamentalist movements. Findings reveal that "The Call to Quran and Sunnah" prioritizes Islamic creed learning, employing a teacher-centered approach, while "Justice and Spirituality" encompasses not only religious matters but also addresses social and political issues through a learner-centered approach. Moreover, as both movements rely on social media and the internet to expand their educational program, some limitations affect the achievement of an ideal Islamic learning environment.